PENGEMBANGAN APLIKASI ANDROID UNTUK E-COMMERCE PRODUK AGRO DENGAN DATABASE MYSQL DALAM RANGKA MEMPERKUAT KETAHANAN PANGAN DI PROVINSI BANTEN - Muhammad Iman Santoso; Wahyu Susihono (Leuit (Journal of Local Food Security), 2020)
Android application is designed for agro product E-Commerce that utilize the MySQL database. This application aims to help the Banten Provincial Government to realize the target of corn self-sufficiency in Banten by connecting farmers directly with their consumers. Java, XML, and PHP are used to develop this application. The E-Commerce adheres to the type of C2C system where third party accounts are employed in the transaction. It has a multi-level user system where anyone can register as a seller, buyer, or transportation service. Sellers and transportation services can directly promote their goods in this system. After clicking the button on the application, the Buyers can immediately make transactions quickly, safely, and comfortably. BlackBox and compatibility testing were carried out and produced 100% success. It is indicated that our application is suitable for the digital corn trade management system in Banten to strengthen food security.